Selection, intake, and plate waste patterns of leftover food items among U.S. consumers: A pilot study - Roe, Brian E.; Qi, Danyi; Apolzan, John W.; Martin, Corby K. (PLOS ONE, 2020)
Many campaigns promote the preservation and consumption of leftover food items as a critical household strategy to accomplish national consumer food waste reduction goals. We fill a gap in knowledge about the consumption and creation of leftovers in the United States by analyzing data from a pilot study in which 18 subjects tracked food selection, intake, and plate waste across all eating occasions for about one week. Subjects noted which items selected for consumption were leftovers, i.e., previously prepared but uneaten items that were stored for future consumption, and which unfinished items were saved to become leftovers. We found that 12% of items selected for consumption were leftovers while 24% of selected items that were not fully consumed were kept to become a leftover. Leftovers were most frequently vegetables, cheeses, and meats, and most frequently selected on Mondays and for lunch. Regression analyses isolate significant dining patterns with respect to leftovers, including evidence that leftovers were less likely to be fully consumed than non-leftover items, and that larger meals led to more uneaten food. This suggests that strategies to reduce meal size may be most effective in reducing food waste by limiting the creation of leftovers in the first place. Strategies to make leftovers more attractive and appealing may also reduce food waste.